Lip swelling and constipation: Pretest probability of cutaneous signs for crohn's disease in the absence of typical gastrointestinal symptoms - Maggie L Chow; Minnelly Luu (Wolters Kluwer Medknow Publications, 2020)
We describe a female child in the first decade patient admitted to a children's hospital for lip swelling and constipation who was ultimately diagnosed with Crohn's disease. Her lip swelling resolved after the initial immunosuppression for her Crohn's disease. In this article, we discuss the pretest probability of cutaneous findings associated with inflammatory bowel disease in predicting a diagnosis of Crohn's disease in the absence of intestinal symptoms. Cutaneous findings including linear immunoglobulin A bullous dermatosis, pyoderma gangrenosum, lichen spinulosus, and epidermolysis bullosa acquisita are discussed.